Understanding genetics DNA, genes, and their real-world applications - Sadava, David E.; Teaching Company (Springfield, VA : Teaching Co., 2008)
"Understanding genetics is like sitting down to work a massive puzzle. With each piece you examine, think through, and solve, you glean a new and amazing insight into humanity. Put several pieces together, and you can treat or cure a disease, save a developing fetus from a fatal birth defect, catch a criminal, or reunite a family ... Each lecture begins with a helpful story that illustrates the importance of genetics. The course explicitly outlines the connections between the science of genetics and the health-related problems that plague us in modern society, and illuminates how studying genetics can be instrumental in solving those problems."--Publisher's website.
pt. 2. Disc 1, lecture 13. Biotechnology and the environment ; lecture 14. Manipulating DNA by PCR and other methods ; lecture 15. DNA in identification: forensics ; lecture 16. DNA and evolution ; lecture 17. DNA and human evolution ; lecture 18. Molecular medicine: genetic screening -- disc 2, lecture 19. Molecular medicine: the immune system ; lecture 20. Molecular medicine: cancer ; lecture 21. Molecular medicine: gene therapy ; lecture 22. Molecular medicine: cloning and stem cells ; lecture 23. Genetics and agriculture ; lecture 24. Biotechnology and agriculture.
DVD.
24 lectures, 30 min. each (6 per disc).
Keywords: Genetics -- Videos (DVD); Genetics -- Study and teaching -- Videos (DVD); Medical genetics -- Videos (DVD); DNA -- Videos (DVD); Biotechnology -- Videos (DVD)